Partial factor IX protein in a pedigree with hemophilia B due to a partial gene deletion. - Bray, G L (1986)
A partial gene product was identified in a pedigree with hemophilia B due to a partial deletion of the Factor IX gene (Chen, S.-H.,S. Yoshitake, P.F. Chance, G.L. Bray, A.R. Thompson, C.R. Scott, and K. Kurachi, 1985, J. Clin. Invest., 76:2161-2164). Levels of this mutant protein in plasma of affected family members studied ranged from 24 to 36 ng/ml (0.6-0.9 U/dl or percent of normal) by a solid-phase immunoassay which is sensitive and specific for the calcium-dependent conformation of human Factor IX. No Factor IX antigen could be detected in patients' plasmas by a non-calcium-requiring monoclonal anti-Factor IX antibody (less than 2 ng/ml). The unconcentrated urine from the five affected family members and four obligate heterozygotes the five affected family members and four obligate heterozygotes tested contained calcium-dependent Factor IX antigen levels ranging from 64 to 160 ng/ml (1.6-4.0 U/dl) and from 10 to 68 ng/ml (0.25-1.7 U/dl), respectively. Of nine normal volunteers screened, three had detectable calcium-dependent antigen in unconcentrated first morning-voided urines with 9.6-16.8 ng/ml (0.24-0.42 U/dl), while the remaining six had detectable urinary antigen only after a 10-fold concentration. Abnormal and normal urinary Factor IX antigen species were concentrated, immunoaffinity purified, electrophoresed, immunoblotted, and distinguished by autoradiography after incubation with 125I-polyclonal calcium-requiring anti-Factor IX. After reducing purified or concentrated samples, a single abnormal 36,000-mol-wt band was identified in the urines from the four affected family members and four obligate heterozygotes tested. Electrophoresis of the reduced urinary Factor IX antigen from the one normal subject tested showed a broad 15,000-20,000-mol-wt band. This normal band was smaller than the species in patients' urines, and was seen as a minor component in the samples from the heterozygotes. No abnormal antigen could be detected in urine from the two other female family members tested. Thus, abnormal urinary Factor IX antigen represents a marker for the presence of the hemophilic Factor IX gene in this family.